SAT0059 Baseline Interleukin-17A PREDICT Treatment Response to TOCILIZUMAB and Disease-Modifying Antirheumatic Drugs Therapy. (10th June 2014) - Lee, S.J.; Yoon, M.J.; Joo, S.H.; Park, W.; Park, S.H.; Shim, S.C.; Baek, H.J.; Yoo, D.-H.; Kim, H.A.; Lee, S.K.; Lee, Y.J.; Park, Y.E.; et al.
Abstract : Background: Tocilizumab (TCZ) has been developed and investigated in several clinical trials for efficacy and adverse events in RA patients. But it remains to be investigated which biomarkers have early predictive values. Objectives: To investigate predictive cytokines of TCZ therapy in rheumatoid arthritis (RA) patients with an inadequate response to disease-modifying antirheumatic drugs (DMARDs). Methods: We collected sera as part of CWP-TCZ301, a 24-week, randomized, double–blinded trial of TCZ in RA patients with an inadequate response to DMARDs. Serum levels of cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-17A, IL-21 and IL-23 were determined by luminex multiplex analysis at baseline and after treatment (4, 12 and 24 weeks). IL-6 and soluble IL-6 receptor (sIL-6R) were measured by ELISA. Therapeutic response was evaluated by American College of Rheumatology 20% improvement (ACR20) in the TCZ group (n=47) and placebo group (n=48) after 24 weeks. Results: Early withdrawal patients from the study were excluded in the evaluation. In TCZ group (n=40), 29 patients were ACR20 responders and 11 patients were non-responders after 24 weeks of treatment. Baseline serum levels of IL-17A were significantly lower in responders than in non-responders ( p <0.05). However IL-17A level did not significantly change during TCZ treatment irrespective of ACR20 response. Levels of IL-21 and IL-23 were not significantly different at baseline in responders and non-responders. However, they were significantly decreased at 12 and 24 weeks in responders (all p <0.005), but not in the non-responders. In the placebo group (n=43), 8 patients were ACR20 responders and 35 patients were non-responders after 24 weeks of treatment. Baseline serum levels of IL-17A and IL-21 in ACR20 responders were significantly lower than in non-responders (p<0.001 and p=0.001, respectively). But they did not significantly change during DMARDs treatment, irrespective of ACR20 response. Multivariable logistic regression analysis showed that lower baseline IL-17A patients had increased the odds ratio of being a responder after TCZ (OR 7.364) as well as placebo (OR 9.333) treatment. Conclusions: Baseline serum level of IL-17A could be used to predict response of TCZ and DMARDs therapy in RA patients. References: Zhou L, Ivanov, II, Spolski R, Min R, Shenderov K, Egawa T, et al. IL-6 programs T(H)-17 cell differentiation by promoting sequential engagement of the IL-21 and IL-23 pathways. Nat Immunol 2007;8(9):967-74. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5095